Perinatal Cells: A Promising COVID-19 Therapy? - Papait, Andrea; Cargnoni, Anna; Sheleg, Michal; Silini, Antonietta R.; Kunis, Gilad; Ofir, Racheli; Parolini, Ornella (Frontiers in Bioengineering and Biotechnology, 2021)
The COVID-19 pandemic has become a priority in the health systems of all nations worldwide. In fact, there are currently no specific drugs or preventive treatments such as vaccines. The numerous therapies available today aim to counteract the symptoms caused by the viral infection that in some subjects can evolve causing acute respiratory distress syndromes (ARDS) with consequent admission to intensive care unit. The exacerbated response of the immune system, through cytokine storm, causes extensive damage to the lung tissue, with the formation of edema, fibrotic tissues and susceptibility to opportunistic infections. The inflammatory picture is also aggravated by disseminated intravascular coagulation which worsens the damage not only to the respiratory system, but also to other organs. In this context, perinatal cells represent a valid strategy thanks to their strong immunomodulatory potential, their safety profile, the ability to reduce fibrosis and stimulate reparative processes. Furthermore, perinatal cells exert antibacterial and antiviral actions. This review therefore provides an overview of the characteristics of perinatal cells with a particular focus on the beneficial effects that they could have in patients with COVID-19, and more specifically for their potential use in the treatment of ARDS and sepsis.